1989
DOI: 10.1007/bf00717739
|View full text |Cite
|
Sign up to set email alerts
|

Estimation ofpA2 values at presynaptic ?2-autoreceptors in rabbit and rat brain cortex in the absence of autoinhibition

Abstract: An attempt was made to determine pA2 values of antagonists at the presynaptic, release-inhibiting alpha 2-autoreceptors of rabbit and rat brain cortex under conditions when there was very little released noradrenaline in the autoreceptor biophase and, hence, pA2 values were not distorted by endogenous autoinhibition. Cortex slices were preincubated with 3H-noradrenaline and then superfused and stimulated by trains of 4 pulses delivered at 100 Hz or, in a few cases, by trains of 36 pulses at 3 Hz. The alpha-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…The S2/Si, S3/S1, and S4/SI ratios in agonist-free control experiments in tissue from EEDQ-treated rats were in the range of 0.96-1.02, 0.92-0.99, and 0.92-0.99, respectively. Thus, there was no significant change in the electrically evoked overflow of tritium over time (see also Limberger et al, 1989).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The S2/Si, S3/S1, and S4/SI ratios in agonist-free control experiments in tissue from EEDQ-treated rats were in the range of 0.96-1.02, 0.92-0.99, and 0.92-0.99, respectively. Thus, there was no significant change in the electrically evoked overflow of tritium over time (see also Limberger et al, 1989).…”
Section: Resultsmentioning
confidence: 93%
“…The slices were then incubated for 30 min at 37C in 2 ml of medium containing 0.125 ILM (-)-[3H]-NA (specific activity 40 Ci mmol' ), washed twice and transferred to superfusion chambers which were equipped with platinum wire electrodes 5 mm apart . The slices were placed on a polypropylene mesh between the electrodes and superfused at 37C and a flow rate of 0.7 ml min-' (one slice per chamber, 12 chambers in parallel; Ismatec IPS-16 peristaltic pump, Zurich, Switzerland which is also denoted 'POP' (pseudo-one-pulse; Singer, 1988 Limberger et al, 1989).…”
Section: Preparation Of Tissue Incubation and Superfusionmentioning
confidence: 99%
“…Studies on presynaptic a-autoreceptors also first indicated heterogeneity within the 2 class (Doxey & Everitt, 1977;Dubocovich, 1979). A species difference between the rabbit and the rat, for example, was a consistent finding (Reichenbacher et al, 1982;Ennis, 1985;Lattimer & Rhodes, 1985;Alabaster et al, 1986;Limberger et al, 1989).…”
Section: Introductionmentioning
confidence: 78%
“…The outflow of tritium was expressed as fractional rate (min-'). The stimulation-evoked overflow was calculated by subtraction of the basal outflow and was expressed as a percentage of the tritium content of the tissue (Limberger et al, 1989;. For further evaluation of basal tritium efflux, ratios were calculated of the fractional rate during the 5 min before S2, S3 and S4, and the fractional rate during the 5 min before SI (b2/b1, b3/b1, b4/b1).…”
Section: Methodsmentioning
confidence: 99%
“…This was achieved by stimulating the tissue with short (91 ms) trains of electric pulses, too short to allow autoinhibition to develop (Singer, 1988). Autoinhibition-free conditions are required for valid determination of dissociation constants (Fuder et al, 1983;Limberger et al, 1989;see Starke et al, 1989).…”
Section: Resultsmentioning
confidence: 99%